Integrated chemo‐ and biocatalytic processes: a new fashion toward renewable chemicals production from lignocellulosic biomass. Issue 2 (5th October 2022) - Chen, Zhu; Wang, Yuguang; Cheng, Haina; Zhou, Hongbo
Abstract: Concerns over climate change and environmental pollution resulting from petroleum refining has spurred the exploitation of green replacements for producing chemicals and fuels. Valorization of lignocellulosic biomass into chemicals represents a promising alternative to petroleum refining. Biological and chemical catalysis are two leading routes for lignocellulose variolization, but strategies relying simply on biological or chemical conversion have shown limitations. Integrating biocatalysts with chemocatalysts could leverage the inherent strengths of both while circumventing their respective disadvantages, benefiting product yield and selectivity, and reducing cost and waste generation. This review focuses on the coupled chemocatalytic and biocatalytic synthesis of renewable chemicals from polysaccharides and their derived platform chemicals. In addition, strategies for producing value‐added products from lignin via integrated chemical depolymerization and biological conversion are highlighted. The techno‐economics of integrating chemocatalysts and biocatalysts in producing chemicals in the context of biorefinery are also discussed. Finally, perspectives on designing integrated chemical and biological catalysis for renewable chemicals production are provided. © 2022 Society of Chemical Industry (SCI).